Contribuições da Teoria da Complexidade para a análise de práticas de letramento bilíngue português-alemão - Guimarães, Thais Steffen (Universidade do Vale do Rio dos Sinos, 2021)
Working with Bilingual Education requires continuous and intensive study in order to provide meaningful teaching practices to students. Thus, the theme of this dissertation is Portuguese/German bilingual literacy as a complex system, in a 2nd year class of Elementary School I. Therefore, this work presents the following research questions: How teachers and families help to develop literacy practices in a bilingual Portuguese/German environment? How can Complexity Theory help us understand bilingual literacy? The objective is to verify which literacy practices are carried out in bilingual Portuguese and German education by the school and the family and how we can understand them in the light of the Complexity Theory. The research, which is qualitative and ethnographic in nature, focuses on observing classes and conducting interviews with the class teacher, three students and their parents in order to learn about literacy practices carried out at home and at school. This study is based on the Theory of Complexity, especially regarding the studies conducted by Larsen-Freeman (2009, 2011), Cameron and Larsen-Freeman (2007, 2008), Franco (2013), and Paiva (2011), which approach language as a complex system. Aspects about bilingual education are also addressed from references such as Megale (2019), García (2009, 2014). In the area of literacy, we highlight Hornberger (2003), Kleiman (2010, 2012, 2014), Rojo (2009, 2019), Soares (2017) and Tfouni (2010). Data analysis was carried out following classroom observations and interviews in the remote mode, due to the care related to the new coronavirus pandemic. As a result, we present a complex analysis of the relationship between bilingual literacy in reading and writing practices and conclude that the interaction between systems and agents inserted in different contexts influences the complexity and dynamics of the literacy practices provided that are very important for motivation and for student engagement in reading and writing activities.
Keywords: Letramentos; Ensino bilíngue; Alemão; Teoria da Complexidade; Literacies; Bilingual education; German; Complexity Theory; ACCNPQ::Lingüística, Letras e Artes::Lingüística